The Compulsory Conciliation Mechanism under the 1982 United Nations Convention on the Law of the Sea in the Settlement of International Maritime Disputes: Application and Legal Coordination - Cheng, Huang Po (VNU Journal of Science: Legal Studies; Vol 41 No 4DO - 10.25073/2588-1167/vnuls.4803, 2025)
This article examines the compulsory conciliation mechanism under the 1982 United Nations Convention on the Law of the Sea (UNCLOS) as a distinctive method for settling international maritime disputes. The mechanism combines the flexibility of political–diplomatic measures with the binding force of a legal framework, thereby balancing legal certainty with political acceptability among the parties concerned. Based on this approach, the study clarifies three core aspects: the scope of application, the competence of the Conciliation Commission, and the legal effect of the conciliation report. It further proposes expanding the Commission’s competence and strengthening the implementation of its reports to ensure fairness and enhance the effectiveness of dispute settlement. The findings not only enrich international legal theory but also carry significant practical implications for maintaining peace, stability, and cooperation in the South China Sea.